(untitled) (Bangladesh Medical Journal, 2016)
Iron deficiency anemia is considered as one of the major public health problem in Bangladesh. Cardiac autonomic nerve dysfunction may present in iron deficiency anemia which increases the risk and further complications of this disease. Assessment of heart rate variability (HRV) is a non-invasive technique to evaluate cardiac autonomic nerve function status. To assess the cardiac autonomic nerve function status by heart rate variability analysis, 100 female subjects with iron deficiency anemia aged 20-45 years were included in the study group. For comparison, age and sex matched 100 apparently healthy female were selected as control. The HRV parameters were recorded by a 4 active channels, Polyrite-D. Mean resting pulse rate, LF power, LF norm and LF/HF were significantly (p <0.0001) higher and total power, HF power, HF norm were significantly (p <0.0001) lower in subjects with iron deficiency anemia in comparison to those of control group. This study concludes that cardiac parasympathetic activity was reduced in female with iron deficiency anemia. Bangladesh Med J. 2014 Sep; 43 (3): 125-129